Sonication-supported synthesis of cobalt oxide assembled on an N-MWCNT composite for electrochemical supercapacitors via three-electrode configuration - Rajendra Kumar Nare; Sivalingam Ramesh; Praveen Kumar Basavi; Vijay Kakani; Chinna Bathula; Hemraj M.Yadav; Prakash Babu Dhanapa; Rama Krishna Reddy Kotanka; Visweswara Rao Pasupuleti (Springer Nature, 2022)
The Co₃O₄@N-MWCNT composite was synthesized by a sonication-supported thermal reduction process for supercapacitor applications. The structural and morphological properties of the materials were characterized via Raman, XRD, XPS, SEM–EDX, and FE-TEM analysis. The composite electrode was constructed into a three-electrode configuration and examined by using CV, GCD and EIS analysis. The demonstrated electrochemical value of ~ 225 F/g at 0.5A/g by the electrode made it appropriate for potential use in supercapacitor applications.